Price versus tradable quantity regulation. Uncertainty and endogenous technology choice - Halvor Briseid Storrøsten (Statistics Norway, Research Department, 2011)
This paper shows that tradable emissions permits and an emissions tax have a risk-related technology choice effect. We first examine the first- and second-order moments in the probability distributions of optimal abatement and production under the two instruments. The two instruments will, in general, lead to different expected aggregate production levels when technology choice is endogenous, given that regulation is designed to induce equal expected aggregate emissions. Moreover, either regulatory approach may induce larger variance in optimal production and optimal abatement levels, depending on the specification of the stochastic variables. Finally, because firms' valuation of a flexible technology increases if the variance in abatement is inflated and vice versa, either of the two instruments may induce the most flexible technology. Specifically, a tax encourages the most flexibility if and only if abatement costs and the equilibrium permit price have sufficiently strong positive covariance compared with the variance in the price on the good produced.
Keywords: H23; Q55; Q58; 330; Regulation; Technology choice; Uncertainty; Investment.